(untitled) - Shepard, Glenn (Hoboken, N.J., 2005)
It includes ready-to-use evaluation forms and plenty of sample material for designing your own forms. Plus, there's more: legal issues and anti-discrimination laws, planning and organizing evaluations, avoiding managerial bias and stereotyping in evaluations, designing fair and reasonable evaluation forms, rating and scoring completed forms, conducting employee self-evaluations, evaluating different employee personality types, sample phrases and words for writing evaluation forms.
Keywords: Employees; Rating of